Exploring the Therapeutic Potential of Moringa Oleifera Leaves: Health Benefits and Applications (International Journal of Scientific Research in Science and Technology, 2025)
Moringa oleifera, commonly known as the drumstick tree, has garnered significant attention in recent years due to its impressive array of nutritional and medicinal properties. This research paper provides an in-depth review of the therapeutic potential of M. oleifera leaves, emphasizing their health benefits and diverse applications. The bioactive compounds found in Moringa leaves, including vitamins, minerals, antioxidants, and phytochemicals, play crucial roles in their efficacy for treating and preventing a wide range of health conditions. Specifically, the leaves exhibit potent antioxidant, anti-inflammatory, antimicrobial, and anti-cancer properties, making them valuable in combating chronic diseases such as diabetes, cardiovascular diseases, and certain cancers. Additionally, Moringa leaves are effective in addressing malnutrition and have been extensively used in traditional medicine for various ailments. This review also explores the integration of Moringa leaves into modern medical and nutritional practices, highlighting their potential as nutraceuticals, pharmaceuticals, and functional foods. Further research is warranted to fully elucidate the mechanisms of action and to harness the therapeutic potential of M. oleifera leaves for improving public health on a global scale.